Analysis of Cationic Vitamins in Cell Culture Medium Samples by Capillary Zone Electrophoresis - Debbie van der Burg; Hermann Wätzig; Cari E. Sänger–van de Griend (Journal of Analytical Methods in Chemistry, 2022)
This paper describes a capillary electrophoresis method for the determination of the cationic B-vitamins thiamine, nicotinamide, pyridoxine, pyridoxal, and pyridoxamine in untreated cell culture medium samples. The effects of the buffering capacity, the mobility of the coion, and the preconditioning solution on the robustness of the method were investigated. Using a 100 mM phosphoric acid and 55 mM triethanolamine background electrolyte at pH 2.3 and capillary preconditioning with 1 M NaOH, all five vitamins could be separated with good resolution. Preliminary method validation data over the range 10–110 µM for undiluted samples, with 10 μM being the lower range limit of quantification QL, showed accuracy recoveries of 94–104%, and migration time and peak area repeatabilities within 0.4% RSD and 2.6% RSD, respectively.